Red Propolis as a Source of Antimicrobial Phytochemicals: Extraction Using High-Performance Alternative Solvents - dos Santos, Cíntia M.; de Souza Mesquita, Leonardo M.; Braga, Anna Rafaela C.; de Rosso, Veridiana V. (Frontiers in Microbiology, 2021)
Propolis is a resinous material rich in flavonoids, involved in several biological activities, such as antimicrobial, fungicide, and antiparasitic functions. Conventionally, ethanolic solutions are used to obtain propolis phytochemicals, which restrict their use in some cultures. Given this, we developed an alcohol-free high-performance extractive approach to recover antibacterial and antioxidants phytochemicals from red propolis. Thus, aqueous-solutions of ionic liquids (IL) and eutectic solvents were used and then tested for their total flavonoids, antioxidant, and antimicrobial activities. The surface-responsive technique was applied regarding some variables, namely, time of extraction, number of extractions, and cavitation power (W), to optimize the process (in terms of higher yields of flavonoids and better antioxidant activity). After that, four extractions with the same biomass (repetitions) using 1-hexyl-3-methylimidazolium chloride [C6mim]Cl, under the operational conditions fixed at 3.3 minutes and 300 W, were able to recovery 394,39 ± 36,30 mg RuE.g-1 of total flavonoids, with total antioxidant capacity evaluated up to 7595.77 ± 5.48 µmol TE.g-1dried biomass, besides inhibiting the growth of Staphylococcus aureus and Salmonella enteritidis bacteria (inhibition halo of 23.0 ± 1.0 and 15.7 ± 2.1, respectively). Aiming at the development of new technologies, the antimicrobial effect also presented by [C6mim]Cl may be appealing, and future studies are required to understand possible synergistic actions with propolis phytochemicals. Thereby, we successfully applied a completely alcohol-free method to obtain antimicrobials phytochemicals and highly antioxidants from red propolis, representing an optimized process to replace the conventional extracts produced until now.